Complexes of xylan and synthetic polyelectrolytes. Characterization and adsorption onto high quality unbleached fibres - Mocchiutti, Paulina (2015)
In this work, polyelectrolyte complexes (PECs) were formed by adding polyacrylic acid (PAA) or 4-O-methylglucuronoxylan (Xyl) on poly(allylamine hydrochloride) (PAH) solutions, at different ionic strength and neutral pH. Turbidity curves, charge densities of the cationic complexes determined by polyelectrolyte titration method, and z-potential values showed clear differences between both complexes. Stirring favourably reverses the effects of sedimentation of Xyl/PAH complexes, as demonstrated by colloidal stability tests. Adsorption studies on silica surfaces, performed by Quartz Crystal Microbalance with Dissipation (QCM-D) showed that PAA/PAH adsorbed complexes layers were rigid, while the corresponding Xyl/PAH layers were viscoelastic. Despite the different conformations, both complexes were adsorbed as spherical particles, as observed by Atomic Force Microscopy (AFM). Adsorption isotherms performed on fibre suspensions showed that the ionic strength of the liquid medium determines the amount of PEC retained. Finally, it was found that the papermaking properties were significantly increased due to the addition of these PECs.